Wind tunnel experiments on ground-mounted photovoltaic solar panels - López, A.; Parnás, V.E.; Cataldo, J. (Revista Ingeniería de Construcción, 2019)
Over the last decades, renewable energy resources have gained an increasing interest for human development and, specifically, photovoltaic solar energy has shown a speedy and rising expansion. Several photovoltaic solar panel farms have been built in many countries to take advantage of this energy. Standards and codes for wind load action have not been an adequate tool for evaluating wind load on photovoltaic (PV) solar panels yet; thus, deeper studies on this subject are necessary. This paper presents an experimental study of wind load on a ground-mounted PV panel in a wind tunnel. The model was tested with inclinations of 15° and 23° for different wind attack directions in an open field. The detailed characteristics of pressure distribution of the mean and peak load coefficients on the panel surfaces were obtained. The shape coefficients from the peak loads were obtained using the 3-s (three-seconds) and area-average approach. Pressure coefficient increases are critical for 0° and 180° with an approximated total increasing percentage of 57% and 61% respectively when varying the angle from 15° to 23°.